Ethnobotany of Dacryodes edulis (G.Don) H.J. Lam in Southern Nigeria 2: Practices and applications among Igbo-speaking people - Omonhinmin, Conrad Asotie (Ethnobotany Research and Applications, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; –> <!–[endif] –><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> <![endif]–><span style="font-size: 9.0pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">The Igbos of Southeast Nigeria believe ube (Dacryodes edulis (G.Don) H.J.Lam) originated in the region. The plant is heavily cultivated around homes, homesteads, and village centers as a preferred reception/meeting point. It constitutes a key auxiliary income source for farmers, women, and vendors alike. The whole plant and/or its parts are associated with several practices and applications amongst the Igbo tribal people. It is preferable to soften the fruits with hot ashes and eat it with maize. The people utilize the plant’s medicinal properties for managing a vast number of health conditions. In some areas, the plant is venerated as “pure” or “sacred” because of historical mysterious events linked to it. The idioms and proverbs relating to the plant show the importance of ube in the Igbos cultural system. These connections cut across worship, marriage, birth, chieftaincy/coronation, dispute, recreation, construction, and craftworks. Ardent efforts are required to preserve this rich ethnobotanical knowledge as well as a section of the plant’s (small-sized fruit) germplasm, which is threatened by the prevailing trade and domestication trends that favor large-sized fruit types within and beyond the tribal confines.